Analysis of Relationship Between the Role of Human Resources of Development (HRD) With Nursing Performance in Sri Ratu General Hospital in 2019 - Seri, Maria (UI Scholars Hub, 2021)
Recruitment and development there is an entrance which is crucial for the availability of qualified staff employees. The recruitment process of each company certainly has a different mechanism, the company should carry out recruitment in accordance with applicable regulations. Errors in recruiting employees will result in companies will get employees who are not as expected. Development is a means to improve the mastery of various skills and work implementation techniques, especially to develop intellectual abilities and human personality so that the company's performance is better and makes the company's continuity continue. The purpose of this study was to determine the relationship of the role of HRD in staffing process and staffing development with the performance of nurses in Sri Ratu Hospital in 2019. Thisresearch method is qualitative. Data collection techniques by in-depth interviews, direct observations, documentation and literature review. The population of all Sri Ratu Medan Hospital employees is 60 people. The sample consisted of 5 people (purposive sampling), namely 1 (one) Head of HRD, 1 (one) Head of Nursing, 1 (one) Head of Room, 1 (one) Member I and 1 (one) Member II. Data analysis using Triangulation test. The results of this study indicate that the staffing process and staffing development have improved the performance of nurses at Sri Ratu Medan Hospital so that the role of HRD is crucial for hospital success. It is recommended to HRD Sri Ratu Medan to continue to improve insights in the implementation of recruitment and development so that performance can be even better.